ASSESSING AUDIT TIMELINESS: THE IMPACT OF FIRM SIZE AND AUDIT FEE ON AUDIT REPORT LAG IN INDONESIA - Nuryanti Hendrawati; Lusianty; Ade Imam Muslim (JAT : Journal Of Accounting and Tax, 2025)
Abstract to examine the influence of firm size and audit fees on the duration required to finalise the audit report. This study examines firms in the non-cyclical consumer sector listed on the Indonesia Stock Exchange from 2021 to 2023. The employed method is descriptive and verificative, utilising a quantitative approach. Employing a purposive sampling strategy, 26 companies were chosen as samples, yielding 78 data observations. The data was examined by multiple linear regression analysis utilising SPSS. The research findings indicate that both firm size and audit fees concurrently exert a substantial influence on audit report delay. These two variables exhibit a negative and considerable impact on audit report delay. Consequently. The larger the company and the higher the audit charge, the more expedited the completion of the financial statement audit.